Electrocatalytic reduction of nitrate ions at a poly crystalline SnCu modified platinum surface by using an H+ conducting solid polymer in a sandwich type membrane reactor. Issue 4 (December 2016) - Koay, P.P.; Alam, Md. Saiful; Alam, M.M.; Etesami, Mohammad; Hasnat, Mohammad A.; Mohamed, Norita
Graphical abstract: In a sandwich type membrane reactor, while Sn particles are incorporated with Cu-Pt catalyst, ammonia selectivity is decreased and nitrogen (N2 ) selectivity is increased. Abstract: The electrocatalytic reduction of nitrate ions (NO3 − ) was performed in a neutral medium by using a sandwich type membrane reactor, M ǀ Nafion ǀ Pt–X (where, X = Cu, SnCu). The voltammetric and electrolysis results showed that the performances of catalytic surface were in the order of Pt < Cu–Pt < SnCu–Pt. A Cu–Pt catalyst generated ammonia, conversely, a SnCu–Pt catalyst yielded molecular nitrogen while nitrate ions were reduced. Adsorbed hydrogen atoms in the form of Pt–H species could regenerate the performance of SnCu–Pt catalyst.